Rapid retreat of Berry Glacier, West Antarctica, linked to seawater intrusions revealed by radar interferometry - Chen, Hanning; Rignot, Eric; Scheuchl, Bernd; Milillo, Pietro; Morlighem, Mathieu; Gadi, Ratnakar; Ciracì, Enrico; Kim, Jae Hun; Dini, Luigi (Nature communications, 2025)
We employ a time series of ERS-1/2, ALOS-1/2 PALSAR, Sentinel-1, COSMO-SkyMed, and RCM differential synthetic-aperture radar interferometry data from 1996 to 2023 to document the short and long-term migrations of the grounding line (GL) of Berry Glacier, West Antarctica, a tributary of Getz Ice Shelf that controls 10% of its ice discharge. In 2019–2021, we detected a short-term GL migration of 18.0 ± 0.9 km, which is exceptionally long and implies that the glacier bed is up to 1300 m deeper than previously known. On short time scales, the GL migrates between three states controlled by bed topography. The observed flexing of the glacier suggests that seawater is trapped in the newly formed ice shelf cavity in an irregular fashion during the tidal cycle. From 1996 to 2021, the most inland position of the GL retreated by 18.1 ± 0.4 km, or 0.7 km/year, the ice thickness decreased by 11 ± 1 m/year, the ice sped up by 64 ± 5%, and the glacier lost a total mass of 131 ± 23 Gt. We attribute the rapid retreat to an enhanced ocean heat flux from warm Circumpolar Deep Water (CDW) reaching the grounding line through favorable bathymetry channels, combined with km-sized seawater intrusions beneath the glacier that cause rapid melting of basal ice. Satellite radar interferometry reveals the dramatic retreat of Berry Glacier in West Antarctica. Broad intrusions of warm subsurface water, funneled by seafloor channels along retrograde bed slopes, have driven intense basal melting of the ice, which triggered faster ice flow and ice thinning. The cumulative glacier mass loss of 131 Gt since 1996 is one of the largest in Antarctica.